2019
DOI: 10.3390/rs11192326
|View full text |Cite
|
Sign up to set email alerts
|

A Convolutional Neural Network Classifier Identifies Tree Species in Mixed-Conifer Forest from Hyperspectral Imagery

Abstract: In this study, we automate tree species classification and mapping using field-based training data, high spatial resolution airborne hyperspectral imagery, and a convolutional neural network classifier (CNN). We tested our methods by identifying seven dominant trees species as well as dead standing trees in a mixed-conifer forest in the Southern Sierra Nevada Mountains, CA (USA) using training, validation, and testing datasets composed of spatially-explicit transects and plots sampled across a single strip of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
106
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 158 publications
(108 citation statements)
references
References 97 publications
2
106
0
Order By: Relevance
“…The data in this study were limited in the sample size of this study is 2024, of which 1720 were used for training, and so the effectiveness and success of artificial intelligence models in modeling big data may not have been obtained sufficiently, or a limited number of data may have negative effects on iteration success. However, while data pools in the forest growth and yield modeling studies such as this study remain limited the sample size, data analysis which may consist of millions or even millions of data, also called as big data, may be involved in applications such as forestry image processing such as Hamdi et al (2019), Fricker et al (2019) and Sylvain et al (2019). In the analysis of forestry image processing data based on big data, the effectiveness of deep learning techniques will be even more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…The data in this study were limited in the sample size of this study is 2024, of which 1720 were used for training, and so the effectiveness and success of artificial intelligence models in modeling big data may not have been obtained sufficiently, or a limited number of data may have negative effects on iteration success. However, while data pools in the forest growth and yield modeling studies such as this study remain limited the sample size, data analysis which may consist of millions or even millions of data, also called as big data, may be involved in applications such as forestry image processing such as Hamdi et al (2019), Fricker et al (2019) and Sylvain et al (2019). In the analysis of forestry image processing data based on big data, the effectiveness of deep learning techniques will be even more apparent.…”
Section: Discussionmentioning
confidence: 99%
“…Hansen et al [30] have achieved the individual pig recognition with accuracy rates of 96.7%. Fricker et al [31] have proposed CNNs for the identification of tree species in mixed-conifer forest from hyperspectral imagery, the results demonstrated that the method can accurately identify tree species and predict their distribution. Altuntaş et al [32] have used CNNs to recognize haploid and diploid maize seeds automatically and Zhang et al [33] have proposed a global pooling dilated CNN to identify six common cucumber plant disease.…”
Section: Introductionmentioning
confidence: 99%
“…SVM and RF tend to perform similarly in terms of classification accuracy and training time [29][30][31]. Neural networks are increasingly used in ecological remote sensing studies for their ability to identify trends and patterns from data, model complex relationships, accept a wide variety of input predictor data, and produce high accuracies, at the expense of requiring large amounts of training data [13,[32][33][34]. Tree species classification accuracies reported throughout the literature vary widely from approximately 60% to 95%, along with the type and number of sensors used, biodiversity within forests, and classification methods utilized [6].…”
Section: Introductionmentioning
confidence: 99%
“…NEON data has enabled a new wave of tree detection and classification research, in addition to a need for integrative and reproducible analysis and synthesis [34,37,44,45]. This research has been further accelerated by an ecological data science competition that has tasked research groups with tree crown segmentation, alignment of data, and species classification at the open canopy longleaf pine ecosystem at the Ordway-Swisher Biological Station in Florida [37,46].…”
Section: Introductionmentioning
confidence: 99%